GAMBARAN KARAKTERISTIK KENAIKAN BERAT BADAN BAYI 0 SAMPAI 6 BULAN YANG MENDAPAT ASI EKSKLUSIF PUSKESMAS TELADAN MEDAN - RHIKA ARISTIA SYAFITRI TAMBUNAN; IKA NOPA NASUTION (JURNAL ILMIAH MAKSITEK, 2021)
Using descriptive method with non-probability sampling taken by purposive sampling, that is sampling based on taking casesor respondents who happened to be or were available at the time of the study. From the research results obtained by babiesbased on gender characteristics that there are more males than female babies. With male sex, there are 35 babies (58.35).Based on the characteristics of the tribe that the most tribal namely the Batak tribe numbered 43 babies (71.7%). Based onthe characteristics of religion that the most religion is Christianity amounted to 31 babies (51.7%). Based on thecharacteristics of the number of siblings that the number of siblings 1, numbered 30 babies (50%). Based on the age at birththat all babies born at term with 60 babies (100%). And from the results of an average baby's weight gain 0 to 6 months, theweight gain is within normal limits. Distribution based on sex that the number of men is more than the number of women.Distribution based on the tribe that the Batak tribe more so that the distribution based on religion that Christianity is morethan the religion of Islam. Distribution based on the number of siblings that there are only 1 baby with more siblings than thenumber of siblings 2 or> 3. Distribution based on age at birth that all babies born at term. The average increase in infantweight is 0 to 6 months that babies with exclusive breastfeeding experience normal weight gain.